Ghana : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Ghana. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Ghana's Request for Disbursement Under the Rapid Credit Facility (RCF). Growth is slowing down, financial conditions have tightened, and the exchange rate is under pressure. This has resulted in large government and external financing needs. The authorities have timely and proactively responded to contain the spread of the coronavirus disease 2019 pandemic in Ghana and support affected households and firms. The IMF continues to monitor Ghana's situation closely and stands ready to provide policy advice and further support as needed. The uncertain dynamics of the pandemic creates significant risks to the macroeconomic outlook. Ghana continues to be classified at high risk of debt distress. The authorities remain committed to policies consistent with strong growth, rapid poverty reduction, and macroeconomic stability over the medium term. Additional support from other development partners will be required and critical to close the remaining external financing gap and ease budget constraints.